Integrated multi-omics reveals the molecular mechanisms underlying efficient phosphorus use under phosphate deficiency in elephant grass (Pennisetum purpureum) - Luo, Jiajia; Cai, Zeping; Huang, Rui; Wu, Yuanhang; Liu, Chun; Huang, Chunqiong; Liu, Pandao; Liu, Guodao; Dong, Rongshu (Frontiers in Plant Science, 2022)
Phosphorus (P) is an essential macronutrient element for plant growth, and phosphate (Pi) deficiency limits plant growth and yield. Elephant grass (Pennisetum purpureum) is an important fodder crop cultivated widely in the tropical and sub-tropical areas worldwide. However, the mechanisms underlying efficient P use in elephant grass under Pi deficiency remain poorly understood. In this study, the physiological and molecular responses of elephant grass leaves and roots to Pi deficiency were investigated. The results showed that dry weight, total P concentration, and P content decreased in Pi-deprived plants, but acid phosphatase activity and P utilization efficiency (PUE) increased, compared with Pi-sufficient plants. Regarding Pi starvation-responsive (PSR) genes, transcriptomics showed that 59 unigenes involved in Pi acquisition and transport (especially 18 purple acid phosphatase and 27 phosphate transporter 1 unigenes), 51 phospholipase unigenes involved in phospholipids degradation or Pi-free lipids biosynthesis as well as 47 core unigenes involved in phenylpropanoids and flavonoids biosynthesis were significantly up-regulated by Pi deprivation in leaves or roots. Furthermore, 43 unigenes related to Pi-independence or inorganic pyrophosphate (PPi)-dependent bypass reactions were markedly up-regulated in Pi-deficient leaves, especially 5 UDP-glucose pyrophosphorylase and 15 phosphoenolpyruvate carboxylase unigenes. Consistent with PSR unigene expression changes, metabolomics revealed that Pi deficiency significantly increased metabolites of Pi-free lipids, phenylpropanoids and flavonoids in leaves and roots, but decreased phospholipid metabolites. This study reveals the mechanisms underlying the responses to Pi starvation in elephant grass leaves and roots, which provides candidate unigenes involved in efficient P use and theoretical references for the development of P-efficient elephant grass varieties.